Labour shortage in Malaysian construction industry: Factors affecting recruitment and policy recommendation - Chin, Chee Peng (2023)
Malaysia's construction market is segmented by commercial, residential, industrial, infrastructure sectors, and additional new construction projects. The scope of the construction industry is very wide, unlike manufacturing, agriculture, and servicing sectors which operate in a sport for their operation. Construction projects move from one location to another location after the completion of a task. The building process starts with paper planning, design, financing, recruitment of the workforce, and continues until a structure is built and ready for use. Construction also covers repairs and maintenance work including expansion, extension, and improvement works on the asset, which also eventually involve demolition, dismantling, or decommissioning works (Mordorintelligence, 2022). Over the years, the shortage of local labour and its involvement in the construction industry had caused the over-dependency on foreign workers. Foreign workers become the dominant workforce of the sector. The situation becomes complicated, and it has never improved due to the fast-changing global environment in economics, socioeconomic and politics with the source country. The Covid-19 pandemic is an unprecedented crisis for the global market. The postpandemic market is full of changes and challenges to most of the world economy. We witnessed the downfall of a lot of businesses due to mobility restrictions, disruption of the supply chains, and market lockdown by various countries during the crisis. The shutdown of borders, the lack of business activities, and the migration of human resources to the gig economy had become the main problem in getting the required workforce. Due to the tightening policy after the emergence of the new government in 2018, most of the business sectors are facing a shortage of manpower. The situation worsened when the Covid-19 pandemic caused the closing of countries’ borders, lockdown to reduce human mobility, suspension of projects, and workers getting unemployed with the widespread disruption of economic activities. The construction industry has been facing the problem of labour shortage since the market is fully opened in April 2022 and progressing toward recovery. As the construction industry is the main driving factor of an economy, the problem requires immediate attention. The objective of this research is to do a finding of the cause, the problem, the challenge, and measures to overcome the problem of labour shortage in Malaysia. The study will explore the factors affecting recruitment of labour, the short-term and long-term measures to curb the problem. The data used in this research paper is based on the latest statistical data available from the Construction Industry Development Board (CIDB), the Department of Statistics, and government agencies. The challenges and most significant problems faced by the Malaysian construction industry are identified and analyzed through the collection of information from the press, interviews, and literature reviews. Other than the secondary data from various sources, a questionnaire survey was chosen as a methodology to achieve the objective of the research. The respondents comprising of top management, project manager, and owners from Public-listed companies (PLC), property development companies, infrastructure construction companies, building construction companies, sub-sectors, and those who are involved directly in the industry. For effective analysis, an integrated approach of grounded theory and thematic analysis is being adopted. As construction sector had contributed to more than 6% growth in Malaysian Gross Domestic Production (GDP). It is one of the crucial economic sectors that can provide a dynamic force to provide the overall prosperity of a country. The problem of shortage in labour must be addressed to maintain its competitiveness and healthy growth. The paper intended to provide some possible solutions on how to solve the problem of high dependency on foreign labours and eventually overcome the challenges. It also examines the cause and challenges of the labour shortage in the construction industry and explores more exerted measures to overcome the problem to offer practical implications to the stakeholders and policymakers related to the construction industry. A long-term plan for dealing with the challenges is most important to maintain a steady upward momentum of the industry.